Coupled multiscale-modeling of microwave-heating-induced fracturing in shales. (December 2020) - Cui, Guanglei; Chen, Tianyu; Feng, Xiating; Chen, Zhongwei; Elsworth, Derek; Yu, Hongwen; Zheng, Xu; Pan, Zhejun
Abstract: Microwave heating may be used to stimulate fracture formation and the release of hydrocarbons in gas shales. Although extensively studied experimentally and numerically, the microscopic observations are not fully explained in current work where the heating, at sample-scale, and fracturing, at the mineral-scale, are represented independently. Furthermore, the geometry, structure and mechanical interaction of different minerals are not fully considered in current approaches. We present a novel simulation approach to investigate the coupled electromagnetic-heating-stress-damage process. Microwave heating is simulated at sample-scale and the resulting stress-damage response is examined at micro-scale where minerals with contrasting thermo-mechanical characteristics are stacked as lamellae, instead of nested internally as in previous representations. A three-stage temperature evolution profile is observed in the shale samples – although some stages may be absent in other rocks. The mathematical model accounts for the three modes of stress generated between minerals: horizontal stress ( σ h ) (tensile stress parallel to the grain-grain interface) and the normal stress( σ n ) (tensile stress normal to the grain-grain interface) applied on the minerals, and the shear stress ( τ ) applied on the interface between different minerals. The minerals comprising the shale matrix are categorized into three types – 'high', 'intermediate' and 'low' – conversion efficiency based on their susceptibility to thermal stressing from microwave irradiation. Shear damage and intergranular fracture usually occurs for minerals with high dielectric permittivity. Transgranular fracture may feature both in high permittivity minerals, due to the larger induced horizontal stress ( σ h ), and in low permittivity minerals - due to high volume fraction and larger size. The simulation approach is a powerful way to link the macro-scale characterization and heating to micro-mechanisms of rock failure. Also this work provides mineral classification and criteria to define a priori evaluation of the effectiveness of microwave treatment of shales and other mineral aggregates.